Islamic Personal Religiosity as a Moderator of Job Strain and Employee’s Well-Being: The Case of Malaysian Academic and Administrative Staff - Achour, M.; Nor, M.R.M.; Zulkifli, M.Y. (Springer, 2016)
Presently, there is increased in research on job strain and the effects of religiosity on employee well-being. Despite increased recognition of religiosity as a moderator of well-being, limited research has focused on Islamic perspective of moderating job strain. This study examines the moderating effects of Islamic personal religiosity on the relationship between job strain and employee well-being in Malaysian universities. One hundred and seventeen (117) Muslim academic and administrative staff from four public universities were sampled. Data were collected via questionnaires, and our findings show that the effect of job strain on well-being is significant for employees and that personal religiosity of employees contributed to alleviating job strain and enhancing well-being. Thus, the study concludes that Islamic personal religiosity moderates the relationship between job strain and employee well-being.